Product compatibility hinders pre-emptive advertising (2020)
This paper considers competition in systems of complementary products and examines how compatibility affects the use of informative advertising by an incumbent to deter entry. Advertising increases demand for a product; customers become price sensitive and competition increases, pre-empting new market entrants. However, compatibility reduces competition, so incumbent advertising becomes less effective at deterring entry and additional, costly advertising would be required to induce deterrence. Moreover, compatibility increases advertising by a potential entrant; with efficient advertising technology, consumers are informed about all products and the incumbent cannot deter entry by using additional advertising. Therefore, product standardization policies that encourage compatibility can support new market entrants by discouraging pre-emptive advertising strategies. (JEL D21, D43, L13, L15). © 2020 Western Economic Association International